Sensitivity analysis on thermal conductivity characteristics of a water-based bionanofluid flow past a wedge surface - Chan, Sze Qi; Aman, Fazlina; Mansur, Syahira (Hindawi, 2018)
Termobioconvection boundary layer fow in a suspension of water-based bionanofuid holding both nanoparticles and motile microorganisms past a wedge surface was studied. Te governing nonlinear partial diferential equations on reference of the Buongiorno model were transformed into a set of coupled nonlinear ordinary diferential equations. Shooting technique was then used to solve the transformed nonlinear ordinary diferential equations numerically. Te solutions were found to be contingent on several values of the governing parameters. As highlighted, the velocity profle as well as the skin friction coefcient was afected by the pressure gradient parameter, the function of the wedge angle parameter. On the other hand, the temperature, nanoparticle concentration, and density of motile microorganism’s distributions together with its corresponding local Nusselt number, local Sherwood number, and local density of the motile microorganisms change with the thermophoresis and Brownian motion parameter and so Lewis number, Schmidt number, and bioconvection P´eclet number. An experimental scheme together with sensitivity analysis on the basis of Response Surface Methodology (RSM) was applied to examine the dependency of the response parameters of interest to the input parameters’ change. Obviously, local Nusselt number was more sensitive towards the Brownian motion parameter when the Brownian motion parameter was at 0.2 and 0.3. However local Sherwood number was more sensitive towards the Lewis number for all values of Brownian motion parameter. Compatibility found by comparing results between RSM and shooting technique gave confdence for the model’s accuracy. Te fndings would provide initial guidelines for future device fabrication. Finally, the numerical results obtained were thoroughly inspected and verifed with the existing values reported by some researchers.